Peace Education through Agroecology and Organic Farming - Caporali, Fabio (Studia Ecologiae et Bioethicae, 2024)
In this paper, the challenge of peace education appears as an emergent cultural need in a context of conflictual relationships among human beings and between human beings and their life environment. All sectors of human activity, including agriculture, can potentially contribute to building a cultural barrier to a mounting wave of wars. The ecological approach to agriculture through the ecosystem concept is suitable for unveiling the power of cooperation in developing symbiotic relationships between and among agroecosystem components for attaining a balance of ecosystem services (supporting, provisioning, regulating, and cultural). Enhancement of biodiversity within and between cultivated fields is key for the maintenance of sustainable agriculture, land management, and viable rural community. Scaling up cooperation among hierarchical levels of agriculture organisation (field, farm, and regional, national, international landscapes) appears as the most promising solution for developing a coherent framework consistent with building a peaceful attitude for managing both land, food systems, and friendly relationships among human beings. Organic farming is already a certified and appreciated method of agriculture production that has a potential for improving a peaceful attitude when supported by the core principles of Agroecology.